2011
DOI: 10.1097/lgt.0b013e31821a6823
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcomes After Treatment for Cervical Intraepithelial Neoplasia

Abstract: : Despite the small number of cases, this study indicates that excision of the transformation zone is associated with an increased risk of overall preterm delivery and low-birth weight infants in subsequent pregnancies. No significant difference was found between the 2 cervical excision procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
12
1
Order By: Relevance
“…We identified 406 potentially eligible studies that fulfilled the inclusion criteria of this review. 5 12 13 14 15 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 No unpublished studies were identified. We excluded studies without an untreated reference population, 94 95 96 97 98 99 100 101 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 406 potentially eligible studies that fulfilled the inclusion criteria of this review. 5 12 13 14 15 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 No unpublished studies were identified. We excluded studies without an untreated reference population, 94 95 96 97 98 99 100 101 …”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies examined the impact of cold knife conisation, 13 28 29 30 32 33 34 37 60 61 62 82 87 89 10 studied laser conisation, 42 46 47 48 49 51 52 56 76 78 one studied needle excision of the transformation zone. 13 34 studied large loop excision of the transformation zone, 13 39 40 41 44 45 50 55 56 57 58 59 60 62 63 65 66 67 68 69 73 74 76 77 78 80 81 82 83 86 87 88 90 91 eight studied laser ablation, 35 38 39 47 49 54 56 62 one studied radical diathermy, 62 two studied cryotherapy, 31 60 16 studied excision not otherwise specified, 5 12 14 15 53 64 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is a high incidence of minor harms 9 and the potential for future early pregnancy loss or premature labour for women in this age group. [23][24][25][26] Our recommendation for women aged 20-24 years not to undergo screening reflects the low incidence of cervical cancer and associated mortality in this age group (from 2002-2006, incidence 1.3 per 100 000 population, mortality 0.2 per 100 000 population [Appendix 4]); the uncertain benefit of screening for women in this age group, either immediately or at older ages; and the higher risk of false-positive test results (and their associated harms) compared with older women. We conclude that the harms of screening for cervical cancer in women aged 20-24 years outweigh any potential benefits, but we have a ssigned a weak recommendation given the uncertainty of the evidence.…”
Section: Box 1: Grading Of Recommendationsmentioning
confidence: 99%
“…Since 2008, many more studies have looked at the link between cervical conization and neonatal outcomes [36,43,45,47,[49][50][51][52][53]. Most have used comparison groups from the general population [45,47,[49][50][51]. They did not report the type of conization and mostly provided estimates of risk for the different procedures combined [36,45,47,[49][50][51].…”
Section: Neonatal Outcomesmentioning
confidence: 99%
“…Most have used comparison groups from the general population [45,47,[49][50][51]. They did not report the type of conization and mostly provided estimates of risk for the different procedures combined [36,45,47,[49][50][51]. Compared to the general population, women with CIN who underwent treatment, on average, delivered babies with a lower mean birth weight, an increased risk of low birth weight, an increased risk of intensive care unit admission, and mortality, even after controlling for confounding.…”
Section: Neonatal Outcomesmentioning
confidence: 99%